DEVELOPMENT OF ISLAMIC ORGANIZATIONAL CULTURE AS AN ATTRACTION FOR ISLAMIC BANKING CUSTOMERS - Moch. Hoerul Gunawan; Ajeung Silva Syara Noor Silmi Sudrajat; Bahmid I Magi; Muhamad Ridwan (Gunung Djati Conference Series, 2025)
This study aims to examine in depth how the development of Islamic organizational culture can function as an attraction for Islamic banking customers. The research method used is a qualitative approach with data collection techniques through literature studies. Data analysis is carried out descriptively-analytical. The results of the study indicate that Islamic organizational culture that is consistently internalized in the work and service systems can increase positive customer perceptions of the integrity and commitment of Islamic institutions. This culture creates a deeper emotional and spiritual relationship with customers, thus having an impact on increasing trust and loyalty. In addition, the application of Islamic culture has proven effective as a differentiation strategy, especially in targeting segments of Muslim society that prioritize religious values ​​in choosing financial institutions. This study recommends that Islamic banking continue to strengthen its organizational culture through training, internal supervision, and the active involvement of the Sharia Supervisory Board in building applicable and sustainable Islamic values.